Kinerja Pelayanan Publik di Kantor Camat Dumai Timur - Erinaldi Erinaldi (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2021)
The main role of the government towards the people is to provide services in order to meet the needs desired by the community. Likewise, Dumai Timur District office is demanded to provide quality services for the community. To meet these needs requires good and skilled employee performance in supporting the acceleration of service. In its implementation, there are still complaints from some people about convoluted procedures, the absence of certainty in-service time, and less responsive officers. The purpose of this study was to determine the factors that affect service performance at Dumai Timur District office. The theory used in this research is the theory (Ratminto & Winarsih, 2013)which states there are (13) factors that influence service performance, namely service strategies, client-oriented officers/officers, client-oriented service systems, management commitment, formulation of organizational goals, standardization of tasks, team cohesiveness, person-job suitability, technology-job suitability, control reality, role clarity, role conflict, management level. Respondents in the study were all 29 employees with the census sampling technique. Data analysis used descriptive statistics with the Rating Scale measurement scale. The results of the study in the factors that affect the performance of services at Dumai Timur District office are categorized as quite good, with an average of 2236 (65.90%).